Evaluation of suitable reference genes for qRT-PCR normalization in strawberry (Fragaria × ananassa) under different experimental conditions - Zhang, Yunting (BMC Mol Biol, 2018)
BACKGROUND: Strawberry has received much attention due to its nutritional value, unique flavor, and attractive appearance. The availability of the whole genome sequence and multiple transcriptome databases allows the great possibility to explore gene functions, comprehensively. Gene expression profiles of a target gene can provide clues towards the understanding of its biological function. Quantitative real-time PCR (qRT-PCR) is a preferred method for rapid quantification of gene expression. The accuracy of the results obtained by this method requires the reference genes with consistently stable expression to normalize its data. RESULTS: In present study, the expression stability of seven candidate reference genes in diverse sample subsets of different tissues and fruit developmental stages, and plant subjected to light quality and low temperature treatments was evaluated using three statistical algorithms, geNorm, NormFinder, and BestKeeper. Our data indicated that the expression stability of reference genes varied under different experimental conditions. Overall, DBP, HISTH4, ACTIN1 and GAPDH expressed much more stably. PIRUV, ACTIN2 and 18S were not recommended for normalization in given experimental conditions due to low stability. In addition, the relative expression pattern of HY5 (ELONGATED HYPOCOTYL5) was conducted to further confirm the reliability of the reference genes, which demonstrated the correct adoption of reference genes was of great importance in qRT-PCR analysis. CONCLUSIONS: Expression stability of reference genes from strawberry varied across selected experimental conditions. Systematic validation of reference genes prior to calculation of target gene expression level should be done to improve the accuracy and consistency of qRT-PCR analysis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12867-018-0109-4) contains supplementary material, which is available to authorized users.